Self-Induced Injury of The Periodontal Tissues : A Case Report - Vineet Kini; Dilip G Nayak; Ashita S Uppoor (Wolters Kluwer Medknow Publications, 2005)
Self-induced injuries are inflicted based on habit, frequently associated with psychogenic background; related only in manner by which they are produced, bearing no particular anatomic, etiologic or microscopic similarities. The following case report attributes a suspicious periodontal lesion to self - induced injury